USING INNOVATIVE TECHNOLOGIES TO DEVELOP RISKOLOGICAL COMPETENCE IN STUDENT-TEACHERS (World Conference on Agricultural and Earth Sciences, 2026)
In the modern educational landscape characterized by uncertainty and rapid digital transformation, the ability to manage pedagogical risks has become a crucial professional attribute. This article explores the concept of riskological competence among student-teachers and evaluates the effectiveness of innovative technologies in its development. The study emphasizes that traditional pedagogical training often overlooks the preparedness of future educators to face unpredictable classroom scenarios. By integrating simulation technologies, case-based learning, and interactive modeling, higher education institutions can foster a proactive mindset in future teachers, enabling them to identify, assess, and mitigate risks effectively.
Keywords: Riskological competence, student-teachers, innovative technologies, pedagogical risk, higher education, simulation-based learning.